YURISPRUDENTIA: JURNAL HUKUM EKONOMI - Yurisprudentia Yurisprudentia (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Jurisprudentia is published twice a year as a medium of scientific publication in the study and development of sharia economic law. Jurisprudentia contains scientific papers in the form of conceptual articles, research results as well as actual issues that are relevant in the field of sharia law economics. The content of the post is entirely the responsibility of the author. The editor team is entitled to revise the entry into the editorial table for uniform format without altering the content and intent of writing. Editorial Address Faculty of Sharia and Law Science IAIN Padangsidimpuan Jl. H.T. Rizal Nurdin Km. 4.5 Sihitang Padangsidimpuan Telp. (0634) 22080.